Removal of phorbol esters present in Jatropha curcas kernel by fungal isolates - Najjar, Azhar; Abdullah, Norhani; Saad, Wan Zuhainis; Ahmad, Syahida; Oskoueian, Ehsan; Gherbawy, Youssuf (Friends Science Publishers, 2014)
Seed kernel from Jatropha curcas L. cannot be utilized as animal feed due to the presence of toxic phorbol esters. However,biological treatments may alleviate the concentration of phorbol esters to a safe level. In the present study, two fungal isolates obtained from garden soil and five endophytes from Achillea fragrantissima plant in Saudi Arabia were used for treatments of J. curcas kernel. These fungi were identified as Cladosporium cladosporioides (isolate TUC9), Fusarium chlamydosporum (isolates TUF1, TUF10 and TUF11), Paecilomyces sinensis (isolate TUP8) and Trichoderma harzianum (isolates TUT1 and TUT2), based on their morphological characteristics and internal transcribed spacer regions sequence analysis. Fungal extracts at 250 μg mL-1 of all isolates grown in potato dextrose broth (PDB) did not show cytotoxic effect against both human Chang liver and mouse NIH 3T3 fibroblasts cell lines. Treatment of J. curcas kernel in submerged fermentation showed the ability of all isolates to grow in 30 ml PDB supplemented with 14 g ground Jatropha kernel (5.6 g dry matter) containing 15.57 mg phorbol esters. The levels of phorbol esters decreased from 2.78 mg g-1dry matter of kernel to 0.06 mg g-1of spent substrate (97.8%) after 30 d incubation at 28ºC by T. harzianum TUT1. Lipase activity was observed in all fungal isolates, but only P.sinensis TUP8, C. cladosporioides TUC9 and F. chlamydosporum TUF10 showed both lipase and esterase activities. Both enzyme activities were significantly higher (p<0.05) in the presence of phorbol esters.